2019
DOI: 10.2174/1381612824666181010151849
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry, Traditional Uses and Pharmacological Profile of Rose Hip: A Review

Abstract: Background: The fruit of genus Rosa, known as "rose hip", is frequently used in different traditional medicines. Rose hips have long been used to treat kidney stones, gastroenteric ailments, hypertension and respiratory problems such as bronchitis, cough and cold. Aim: This review is focused on the ethnopharmacological uses of rose hip as well as phytochemical and pharmacological aspects. Results: Ethno-medical uses of rose hip have been recorded in many countries since a long time. Approximately, 129 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 0 publications
4
64
1
1
Order By: Relevance
“…Likewise, the data confirm a previous study that reported the presence of catechin, epicatechin, and various other prominent polyphenols (e.g., phlorizin and phloretin) in rose roots and root tips 35 . Gallic acid, commonly acting as an antioxidant, was detected in rose hips 15 . Phlorizin showed a clear trend of higher concentrations in roots grown in G soils (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the data confirm a previous study that reported the presence of catechin, epicatechin, and various other prominent polyphenols (e.g., phlorizin and phloretin) in rose roots and root tips 35 . Gallic acid, commonly acting as an antioxidant, was detected in rose hips 15 . Phlorizin showed a clear trend of higher concentrations in roots grown in G soils (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of secondary metabolites so far carried out in Rosa sp. were related to the pharmaceutical use of roses 15,16 . However, only little information is available about phytoalexins in roses.…”
Section: Introductionmentioning
confidence: 99%
“…We suggest keeping these creams in the refrigerator or, alternatively, to immersing them in ice water before the procedure. Products containing triterpenes of gotu kola with rosehip oil are the best options [ 33 , 45 ]. Use non-ablative energy devices, such as intense pulsed light or the non-ablative erbium:glass fiber 1550 nm laser system, as part of the treatment for photodamaged skin in patients for whom the recovery time due to their occupation needs to be very short or minimal and who cannot have a prolonged desquamation or appearance of dark scabs as occurs with ablative laser or CP.…”
Section: Therapeutic Managementmentioning
confidence: 99%
“…We suggest keeping these creams in the refrigerator or, alternatively, to immersing them in ice water before the procedure. Products containing triterpenes of gotu kola with rosehip oil are the best options [ 33 , 45 ].…”
Section: Therapeutic Managementmentioning
confidence: 99%
“…HPLC analysis has shown R. canina hips extract to be especially rich in the polyphenols hyperoside, astragalin, rutin, (+)-catechin and (-)-epicatechin, gallic acid and poly-hydroxylated organic acids such as quinic acid [28,29]. The phenolic compouds (+)-catechin, (-)-epicatechin, rutin, vanillin, astragalin, phloridzin and gallic acid, identified in hips extract, have been reported as strong scavengers of the ROO - radical [30].…”
Section: Introductionmentioning
confidence: 99%